Antimicrobial susceptibility and β-lactamase production in Bacillus cereus isolates from stool of patients, food and environment samples - Savić, Dejana B; Miljković-Selimović, Biljana; Lepšanović, Zorica; Tambur, Zoran; Konstantinović, Sonja; Stanković, Nemanja; Ristanović, Elizabeta (Vojnosanitetski pregled, 2017)
Background/Aim. Bacillus cereus (B. cereus) usually ingested by food can cause two types of diseases: vomiting due to the presence of emetic toxin and diarrheal syndrome, due to the presence of diarrheal toxins. Systemic manifestations can also occur. The severe forms of disease demand antibiotic treatmant. The aim of this study was to determine the differences in antibiotic susceptibility and β-lactamase activity of B. cereus isolates from stools of humans, food and environment. Methods. Identification of B. cereus was performed with selective medium, classical biochemical test and polymerase chain reaction (PCR) with primers specific for bal gene. Thirty isolates from each group were analysed for antibiotic susceptibility using the disk-diffusion assay. Production of β-lactamase was determined by cefinase test, and double-disc method. Results. All strains identified as B. cereus using classical biochemical test, yielded 533 bp fragment with PCR. Isolates from all the three groups were susceptible to imipenem, vancomycin, and erythromycin. All isolates were susceptible to ciprofloxacin but one from the environment. A statistically significant difference between the groups was confirmed to tetracycline and trimethoprim-sulphamethoxazole sensitivity. A total of 28/30 (93.33%) samples from the foods and 25/30 (83.33%) samples from environment were approved sensitive to tetracycline, while 10/30 (33.33%) isolates from stools were sensitive. Opposite to this result, high susceptibility to trimethoprim-sulphamethoxazole was shown in samples from stools (100%), while isolates from foods (63.33%) and from environment (70%) had low susceptibility. All samples produced β-lactamases. Conclusion. The strains of B. cereus from all the three groups showed high rate of sensitivity to most tested antibiotics, except to tetracycline in samples from human stool and to trimethoprim-sulphamethoxazole in samples from food and environment. The production of β-lactamases was confirmed in all the strains.